Evidence of Bermuda Hot and Wet Upwelling From Novel Three‐Dimensional Global Mantle Electrical Conductivity Image. (11th June 2020) - Li, Shiwen; Weng, Aihua; Zhang, Yanhui; Schultz, Adam; Li, Yabin; Tang, Yu; Zou, Zonglin; Zhou, Zikun
Abstract: A model of electrical conductivity in the mid–mantle transition zone was obtained with improved constraints. An L 1 ‐norm regularization inversion algorithm is proposed here that reduces the influence of noisy data on three‐dimensional geomagnetic depth sounding inversion from C‐ responses. Here the regularization is implemented by using an L 1 ‐norm to measure the predicted data error, which is normalized by the C‐ response covariance, but an L 2 ‐norm is used to measure the regularization term associated with model parameters. The limited‐memory quasi‐Newton method (L‐BFGS) is used to invert for the three‐dimensional electrical conductivity model. The model is discretized by curved rectangular prisms in spherical coordinates. Sensitivity tests show that for good‐quality data contaminated by Gaussian noise, L 1  inversion, which could perform as well as L 2 inversion, can adequately recover the main features of the electrical conductivity structure within the region of data coverage. When data errors are drawn from an exponential distribution, L 1 inversion obtains relatively reliable reconstruction of the electrical structure, even when the noise level is comparable to that of actual C‐ responses. C‐ responses from 129 low‐latitude and midlatitude geomagnetic observatories are inverted using L 1 ‐norm minimization of the data error. The resulting model reveals an electrically conductive feature in the lower mantle transition zone and upper lower mantle that is broadly coincident with that found in previous studies. The reduced influence of data with large variances on L 1 ‐norm misfits, along with inclusion of responses estimated from more observatories, makes L 1 inversion more clearly identify these deep conductive features while identifying previously obscured anoconductive zones. A feature of particular interest is the high electrical conductivity anomaly beneath the Bermuda‐Sargasso Sea region in the mid–mantle transition zone and the uppermost lower mantle. Rock physics analysis indicates that the anomaly is most possibly caused by the wet upwelling material with excessive ~650 K higher temperature, suggesting a narrow tail with a broad head. Plain‐Language Summary: There remains much to discover regarding the geological characteristics of the Bermuda zone. Specialized scientific instruments deployed in various parts of the world, including the Bermuda zone, have been used to measure geomagnetic and electrical conductivity data for several decades. We used customized computer codes to analyze and model the data recorded by these instruments. We detected a region of very high electrical conductivity in the depth range of 410 to 1, 200 km beneath the Bermuda‐Sargasso Sea area. To understand why the electrical conductivity is so high in this region, we also considered recent results from laboratory experiments of the conductivity of materials subjected to high temperature and high pressure. We find that between depths of 520 and 670 km, the studied region is hydrous and also very hot, with temperatures as high as 1, 700°C, exceeding by 300°C the average mantle temperature. From depths of 670 to 1, 200 km, the mantle is also at least 300°C hotter than normal mantle. The occurrence of these higher temperatures suggests that hot and wet material is rising from the deep mantle beneath the Bermuda‐Sargasso Sea area. This hot upwelling may have accumulated in shallow parts of the mantle as well as the crust, leading to phenomena such as volcanic eruptions and changes in the level of the seafloor in the Bermuda zone. Key Points: L1‐norm measured data misfit can enhance 3‐D GDS inversion reliability and resolution of mantle electrical structure New high electrical conductivity anomalies are revealed in the mantle transition zone The Bermuda high electrical conductivity can be caused by excessively hot and wet upwelling with a narrow tail and a broad head